Penerapan Strategi Pendekatan Culturally Responsive Teaching (CRT) dalam Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas XII-5 SMAN 6 Surabaya - Molita, Afni; Widiyanto, Rendik; Ariyanti, Gregoria; Dian, Mariani (Journal of Comprehensive Science, 2024)
This research aims to improve the mathematics learning outcomes of students in grades XII-5 of SMAN 6 Surabaya by applying the Culturally Responsive Teaching (CRT) approach and the Problem Based Learning (PBL) model in differentiated learning on functional transformation materials. The CRT approach used emphasizes cultural integration in mathematics learning to facilitate student engagement according to their cultural context and background. This study uses the Classroom Action Research (PTK) method which is carried out in two cycles. Each cycle consists of stages of planning, action, observation, and reflection. The subjects of this study are 36 students in grades XII-5 of SMAN 6 Surabaya. Data was collected through learning outcome tests and observations that were analyzed using quantitative and qualitative analysis methods. The results of the study showed a significant improvement in student learning outcomes. In the pre-cycle, the percentage of student completion was 22% with an average score of 62.6. In the first cycle, the completeness increased to 91.6% with an average score of 90.7, and in the second cycle the completeness reached 97.22% with an average score of 96.25. In addition, student activity in group discussions also increased during the implementation of cycle II. The conclusion of this study is that the application of the Culturally Responsive Teaching approach in differentiated learning is effective in improving the mathematics learning outcomes of students in grades XII-5 of SMAN 6 Surabaya, especially in the material of functional transformation. The integration of cultural context in learning is proven to be able to increase student motivation, engagement, and understanding of learning materials.